2020
DOI: 10.1017/s0022215120000766
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway morphological changes in obstructive sleep apnoea: effect of age on pharyngeal anatomy

Abstract: ObjectiveTo evaluate the upper airway morphology changes associated with ageing in adult Chinese patients with obstructive sleep apnoea.MethodsA total of 124 male patients diagnosed with obstructive sleep apnoea by overnight polysomnography, who underwent upper airway computed tomography, were enrolled. The linear dimensions, cross-sectional area and volume of the upper airway region and the surrounding bony frame were measured. The association between ageing and upper airway morphology was analysed.ResultsSof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…Chen et al detected a significant correlation between AHI and the subglosso-supraglottic-level parapharyngeal fat pad, independently of BMI and neck circumference parameters [ 51 ]. According to Gao et al, in patients with a BMI over 28 kg/m 2 , a significant positive effect of age on parapharyngeal AT volumes was detected [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al detected a significant correlation between AHI and the subglosso-supraglottic-level parapharyngeal fat pad, independently of BMI and neck circumference parameters [ 51 ]. According to Gao et al, in patients with a BMI over 28 kg/m 2 , a significant positive effect of age on parapharyngeal AT volumes was detected [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“… 13 A study by Gao et al found that the volume of the retropalatal region increased with aging. 14 The authors hypothesized that the aging effect could reduce the tone of the soft palate muscle, increase the soft palate length and shrink the tonsils. In the current study, the oropharyngeal size showed no significant relationship with age.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Aging is also associated with an increased risk of OSA. 9 Elderly patients tend to have a longer pharyngeal airway due to increased length of the soft palate, 22 an inferiorly located hyoid bone, a smaller cross-sectional area at the retropalatal and retroglossal regions, 23 and an increased parapharyngeal fat pad volume. 22 These changes can result in increased airway resistance and, therefore, increase the risk of airway collapse.…”
Section: Anatomical Changes In Airway In Patients With Osamentioning
confidence: 99%